TINJAUAN KRIMINOLOGIS TERHADAP KEJAHATAN YANG MENGHILANGKAN NYAWA - Heri Setiawan, I Komang (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 01, Maret 2014)
The emergence of criminal acts stems began from the implementation of the consequences of prohibited and punishable by the law. The crime arises from the intention of the doer contains in book II of the Criminal Code with a variety of shapes, properties, and its legal consequences. According to the one of chapters in details about crimes against life are set out in section 338-350. The act a crime which against life. In crimes which cause death to a person's life called murder. According to the Criminal Code, the criminal offenses listed in section 338-350 with all the different elements, giving rise to a variety of crimes includes crimes were directly against the human spirit, soul or a new child is born, and crimes directly against children who are still in the womb.
Keywords: Crime, Book of the Law of Criminal Law (KUHP)